THE PRINCIPLE OF THE 'TEMPORARY NATURE' OF PRODUCT-SHARING BUSINESS RIGHTS IN THE PRINCIPAL AGRARIAN LAW: A LEGAL UTILITY PERSPECTIVE ON LOCAL WISDOM - Makkawaru, Zulkifli; Tira, Andi; Abdurrifai, Abdurrifai; Mustari, Ruslan (Siddiq Institute, 2024)
The profit-sharing agreement is one of the rights derived from customary legal practices recognized in the Basic Agrarian Law, albeit categorized as a temporary right due to its perceived elements of coercion. This research aims to assess the extent to which the Basic Agrarian Law maintains its regulations in this temporary form while acknowledging the often detrimental practices to farmers. Additionally, this study seeks to determine how much the concept of local wisdom in the implementation of a profit-sharing-based agricultural system can be considered to meet the elements of legal utility. The research method employed is normative legal research, with data analyzed normatively through the interpretation and discussion of research materials based on laws, legal norms, theories, and legal doctrines related to the core issues. The findings of this research are descriptive, utilizing both primary and secondary data. The research results indicate that, normatively, the Basic Agrarian Law has not undergone revision, thus still regulating temporary business rights, even though, in practice, the temporary basis still involves elements of coercion. Another outcome reveals that the concept of local wisdom in profit-sharing systems must fulfill elements of legal utility. However, in practice, especially concerning the three main factors required by the law, such as a written agreement, profit distribution, and duration of the agreement, it is concluded that they do not meet the principle of legal utility.Â